2011
DOI: 10.1128/jcm.02208-10
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Erythromycin- and Clindamycin-Resistant Streptococcus pyogenes emm 90 Strains in Hawaii

Abstract: We identified 12 erythromycin-and clindamycin-resistant emm 90 group A streptococcus (GAS) isolates during a retrospective invasive disease survey in Hawaii. A comparison with 20 type-matched isolates showed all resistant isolates to be emm 90.4b with the constitutive or inducible macrolide-lincosamide-streptogramin B resistance phenotype (cMLS B or iMLS B ). All isolates had the same pulsed-field gel electrophoresis (PFGE) pattern, suggesting clonal spread.The erythromycin resistance rate (ϳ3%) has been low a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Mortality in NF patients has remained high despite state-of-theart treatment, including b-lactams and protein synthesis inhibitors such as clindamycin. Although emergence of clindamycin-resistant strains has been observed [2,3], we recently showed that protein synthesis inhibitors efficiently inhibited virulence factor activity even in clindamycin-resistant GAS [15]. We now demonstrate that the inhibition of virulence factor activity by IVIG in clindamycinresistant GAS strains is equal to susceptible strains.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Mortality in NF patients has remained high despite state-of-theart treatment, including b-lactams and protein synthesis inhibitors such as clindamycin. Although emergence of clindamycin-resistant strains has been observed [2,3], we recently showed that protein synthesis inhibitors efficiently inhibited virulence factor activity even in clindamycin-resistant GAS [15]. We now demonstrate that the inhibition of virulence factor activity by IVIG in clindamycinresistant GAS strains is equal to susceptible strains.…”
Section: Discussionmentioning
confidence: 59%
“…This high rate has not changed over time. Although no resistance to penicillin has yet been found, increasing numbers of clindamycin-resistant GAS strains are being reported [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…amSPCs were also potent inhibitors of S .pyogenes , which causes pharyngitis and necrotizing fasciitis and can be challenging to treat in patients allergic to betalactams due to increasing clindamycin and macrolide resistance (36-38). Since S. pneumoniae is a predominant cause of childhood upper respiratory tract infections and treatment is compromised by resistance to macrolides and betalactams, we focused our in vivo efforts on this pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Association of erythromycin resistance and emm typing has been documented earlier. emm 12 from Korea and Japan [51], emm 12 and emm75 from Pittsburgh [52], emm 90 from Hawaii [53], emm 4, emm 28, and emm 77 from Western Greece [54] showed strong association with erythromycin resistance. In present study, association is different from earlier workers as emm 49 was constantly associated with the erythromycin resistance.…”
Section: Discussionmentioning
confidence: 99%